DIGITALISASI ORGANISASI DAN DINAMIKA KEPUASAN KERJA: ANALISIS SINTESIS TERHADAP KINERJA KARYAWAN DI ERA TRANSFORMASI DIGITAL - Hartutik, Dwi; Lastri, Novelma; Aditiya, Variza; Musdiana, Andi Desy; Suprasman, Suprasman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Organizational digitalization has transformed workplace dynamics, influencing employee job satisfaction and performance outcomes. This study synthesizes findings from three Indonesian journal studies focusing on digital transformation, digital work environments, and human resource performance in the context of organizational modernization. Using a qualitative literature synthesis approach, the research integrates methodological and empirical insights to explore how digital adoption affects employee behavior and organizational outcomes. The findings indicate that digital technologies improve efficiency, collaboration, and flexibility, which contribute positively to employee performance. However, challenges such as digital competence gaps, technostress, and organizational adaptation remain critical issues. The study highlights that digital leadership, organizational support, and employee capability development play key roles in enhancing job satisfaction during digital transformation. This synthesis contributes to understanding how Indonesian organizations can optimize digital transformation strategies to achieve sustainable employee performance and organizational effectiveness. Keywords: digital transformation, job satisfaction, employee performance, Indonesian organizations. Abstrak: Digitalisasi organisasi telah mengubah dinamika lingkungan kerja dan memengaruhi kepuasan kerja serta kinerja karyawan. Penelitian ini mensintesis temuan dari tiga jurnal Indonesia yang membahas transformasi digital, lingkungan kerja digital, dan kinerja sumber daya manusia dalam konteks modernisasi organisasi. Dengan menggunakan pendekatan sintesis literatur kualitatif, penelitian ini mengintegrasikan wawasan metodologis dan empiris untuk memahami bagaimana adopsi teknologi digital memengaruhi perilaku karyawan dan hasil organisasi. Temuan menunjukkan bahwa teknologi digital meningkatkan efisiensi, kolaborasi, dan fleksibilitas kerja yang berdampak positif terhadap kinerja karyawan. Namun, tantangan seperti kesenjangan kompetensi digital, technostress, dan adaptasi organisasi masih menjadi isu penting. Studi ini menekankan peran kepemimpinan digital, dukungan organisasi, serta pengembangan kompetensi karyawan dalam meningkatkan kepuasan kerja selama proses transformasi digital. Kata Kunci: Transformasi Digital, Kepuasan Kerja, Kinerja Karyawan, Organisasi Indonesia.